НАПІВПРОВІДНИКОВИЙ РЕГУЛЯТОР ДЛЯ КЕРУВАННЯ РЕЖИМАМИ МЕРЕЖІ В РАЗІ ПРЯМОГО ЗАПУСКУ АСИНХРОННИХ ДВИГУНІВ ЗІСТАВНОЇ ПОТУЖНОСТІ - Чиженко, О.І.; Рибіна, О.Б.; Трач, І.В. (Інститут електродинаміки Національної академії наук України, 2019)
The modification of the circuit-technical solution of the semiconductor regulator based on the thyristor compensator of reactive power intended for managing of the transient processes in the electric network, which arise as a result of the start of asynchronous motors of the comparable power, is considered.  The mathematical model for calculation of electromagnetic transients is presented, the use of which allows to estimate the efficiency of developed devices in distribution electrical networks.  The improvement of the control of the electric network modes is shown. The proposed scheme of the TRC in its composition has a cosine condenser battery and does not use passive filters of higher harmonics of currents. References 6, figures 5.